PEMBERDAYAAN EKONOMI KREATIF MELALUI SEMINAR KEWIRAUSAHAAN DAN PELATIHAN PEMBUATAN BANANA ROLL UNTUK MENINGKATKAN SEMANGAT BERWIRAUSAHA DAN BERINIOVASI BAGI MASYARAKAT DUSUN SEJAJAR DESA PAYAMAN KECAMATAN SOLOKURO - Abdullah Zawawi; Siswadi, Siswadi; Fahud Fahruddin; Kholifatur Rosidah; Robiah Adewiyah (Opportunity Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Sware Community service with the theme of entrepreneurship is a program of community service activities that focuses on entrepreneurial activities. Community service in Parallel Hamlet, Payaman Village, Solokuro District, Lamongan Regency by group 7 KKN INSUD which focuses on the problem of the lack of community potential in entrepreneurship which is still lacking so it needs to be motivated and innovated so that it has an entrepreneurial spirit. By going through the Participatory Action Research (PAR) approach, in which this approach is to get results or changes and new innovations that occur to women in parallel hamlets. This entrepreneurial activity assistance is aimed at housewives who are already entrepreneurs or those who have not started their own businesses. This entrepreneurial assistance is through training on making banana rolls, starting from production to marketing and promotion systems, and also providing socialization about entrepreneurship by providing understanding to mothers to foster a creative and innovative entrepreneurial spirit. The result of this series of community service activities is to provide new ideas for making banana rolls and more modern marketing, as well as other results in the form of designs in the form of logos, brands and others